2021
DOI: 10.1029/2020gb006608
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Organic Carbon Burial in the Eastern China Marginal Seas: A Regional Synthesis

Abstract: Marginal seas are important burial centers of both marine and terrestrial organic carbon (OC), accounting for the burial of more than 90% of sedimentary OC in marine environments Burdige, 2005;Hedges & Keil, 1995). These marginal seas receive vast amounts of sediments, freshwater, and nutrients from their adjacent rivers and coastal erosion, especially in those large delta-front estuaries (Bianchi & Allison, 2009;Kuehl et al., 2020). Large seasonal shifts of terrigenous inputs impact sedimentation rates, sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 133 publications
(383 reference statements)
5
58
0
Order By: Relevance
“…Our proto-burial efficiency estimates are broadly comparable to previous findings from the ECMS, but there are also major differences. For example, an average burial efficiency of 11% has been reported for the mud areas of ECMS (Zhao et al, 2021). Another study found a burial efficiency of 10% in the whole ECS (Duan et al, 2017) and 14% in the mud areas of the ECS (Zhao et al, 2021).…”
Section: Proto-burial Efficiency Of Marine Organic Carbonmentioning
confidence: 98%
See 4 more Smart Citations
“…Our proto-burial efficiency estimates are broadly comparable to previous findings from the ECMS, but there are also major differences. For example, an average burial efficiency of 11% has been reported for the mud areas of ECMS (Zhao et al, 2021). Another study found a burial efficiency of 10% in the whole ECS (Duan et al, 2017) and 14% in the mud areas of the ECS (Zhao et al, 2021).…”
Section: Proto-burial Efficiency Of Marine Organic Carbonmentioning
confidence: 98%
“…Most lipid biomarker data were collected from previous studies (n = 227 for surface suspended particles, and n = 258 for surface sediments) (Zhang et al, 2008;Jiang et al, 2012;Tao et al, 2012;Zhao et al, 2013;Fan et al, 2014aFan et al, ,b, 2015Xing et al, 2014Xing et al, , 2016aHu J. et al, 2016;Wu et al, 2016;Wang et al, 2019), while some were measured in this study, i.e., marine lipid biomarkers in surface suspended particles from the BS and northern YS in the June of 2011, part of the samples in the ECS and southern YS in June of 2010 and July of 2013, respectively, and the CRE in July of 2013 (n = 107). In addition, most data of the following parameters were collected from published results: sea surface temperature (n = 273, from five cruises in summer of 2010-2015), salinity (n = 273, from five cruises in summer of 2010-2015), nutrient concentrations [dissolved inorganic nitrogen (DIN), dissolved inorganic phosphorus (DIP) and silicate (Si)] (n = 133, from three cruises in summer of 2011 and 2015) and Chl a (n = 255, from five cruises in summer of 2010-2014) in the surface water (Jiang et al, 2012;Yang et al, 2015;Hu J. et al, 2016;Wu et al, 2016;Tian et al, 2019;Wang et al, 2019), as well as terrestrial biomarker [ (C 27 + C 29 + C 31 ) n-alkanes] contents (n = 226), TOC (n = 200), δ 13 C TOC , mean grain size and sedimentation rate in surface sediments (Zhao et al, 2011(Zhao et al, , 2013(Zhao et al, , 2021Jiang et al, 2012;Tao et al, 2012;Fan et al, 2014aFan et al, ,b, 2015Xing et al, 2014Xing et al, , 2015Xing et al, , 2016aBao et al, 2016;Qiao et al, 2017). Some data were measured using in situ CTD instrument in this study: sea surface temperature and salinity in the ECS in June 2010 and July 2013 (n = 54), and Chl a in the YRE in August 2015 (n = 33).…”
Section: Sample and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations